Avaliação dos patótipos de Escherichia coli circulantes no rebanho bovino e identificação das cepas de STEC isoladas no estado de São Paulo - Spina, Thiago Luiz Belém [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Beef can be an important vehicle for various pathogens to humans, especially Shiga toxin-producing Escherichia coli (STEC), associated to human and animal diarrhea. In this study, the prevalence of different pathotypes of diarrheagenic E. coli, and virulence profiles of STEC were investigated among feces of cattle slaughtered in São Paulo state, southeast of Brazil. From a total of 431 animals, STEC was identified from 116 (26,9%) samples, being 111 (25,8%) STEC eae- and 5 (1,1%) STEC eae+. EPEC pathotype was detected among 20 (4,6%) of animals. The other pathotypes of diarrheagenic E. coli were not identified. Of the 95 STEC isolates assessed for virulence profile, all harbored stx2, while 28 (29,5%) contained stx1. Iha and saa, genes encoding adhesins, were found at 93,7% (89/95) and 66,3% (63/95), respectively. EspP, gene which encoding a protease related with intestinal colonization, was detected in 61,1% (58/95) and ehxA hemolysin was present in 54,7% (52/95). SubAB, nleE and nleB genes were also detected in lower rates. STEC is widespread in cattle herds of São Paulo, containing commonly isolated genes from human pathogens, which reinforces the importance of inspection and surveillance in the slaughterhouses

A carne bovina pode ser um importante veículo de vários patógenos para os humanos, com destaque à Escherichia coli produtora de Shiga-toxina (STEC), associada com diarreia em animais e humanos. Neste estudo, investigou-se em bovinos abatidos no estado de São Paulo, a prevalência dos diferentes patótipos de E. coli diarreiogênica e o perfil de virulência dos isolados de STEC. De um total de 431 animais, STEC foi identificada em 116 (26,9%) amostras de fezes, das quais 111 (25,8%) STEC eae- e 5 (1,2%) STEC eae+. O patótipo EPEC foi detectado em 20 (4,6%) amostras de fezes dos animais testados. Os demais patótipos de E. coli diarreiogênica não foram identificados. Dos 95 isolados de STEC analisados quanto ao perfil de virulência, todos albergavam stx2, enquanto que 28 (29,5%) continham stx1. Os genes iha e saa, que codificam adesinas, foram encontrados em 93,7% (89/95) e 66,3% (63/95), respectivamente. O gene espP, que codifica uma protease que auxilia na colonização intestinal, foi detectado em 61,1% (58/95) e a hemolisina ehxA em 54,7% (52/95). Também foram identificados em menores frequências os genes subAB, nleE e nleB. STEC está amplamente disseminada nos rebanhos bovinos de São Paulo, carreando genes comumente isolados de patógenos humanos, o que reforça a importância da inspeção e fiscalização nos abatedouros
Keywords: Bovino - Doenças; Escherichia coli; Virulencia (Microbiologia); Fatores de virulência; Toxina Shiga